Processes of initial collision and suturing between India and Asia - Ding, Lin; Maksatbek, Satybaev; Cai, FuLong; Wang, HouQi; Song, PeiPing; Ji, WeiQiang; Xu, Qiang; Zhang, LiYun; Muhammad, Qasim; Upendra, Baral (Science China. Earth sciences, 2017)
The initial collision between Indian and Asian continents marked the starting point for transformation of land-sea thermal contrast,uplift of the Tibet-Himalaya orogen,and climate change in Asia.In this paper,we review the published literatures from the past 30 years in order to draw consensus on the processes of initial collision and suturing that took place between the Indian and Asian plates.Following a comparison of the different methods that have been used to constrain the initial timing of collision,we propose that the tectono-sedimentary response in the peripheral foreland basin provides the most sensitive index of this event,and that paleomagnetism presents independent evidence as an alternative,reliable,and quantitative research method.In contrast to previous studies that have suggested collision between India and Asia started in Pakistan between ca.55 Ma and50 Ma and progressively closed eastwards,more recent researches have indicated that this major event first occurred in the center of the Yarlung Tsangpo suture zone（YTSZ） between ca.65 Ma and 63 Ma and then spreading both eastwards and westwards.While continental collision is a complicated process,including the processes of deformation,sedimentation,metamorphism,and magmatism,different researchers have tended to define the nature of this event based on their own understanding,an intuitive bias that has meant that its initial timing has remained controversial for decades.Here,we recommend the use of reconstructions of each geological event within the orogenic evolution sequence as this will allow interpretation of collision timing on the basis of multidisciplinary methods.